STRATEGY FOR IMPROVING PLANNING PERFORMANCE AND STRENGTHENING REGIONAL FINANCE OF FAKFAK DISTRICT (Overview of Innovation Factors and Competency of State Civil Apparatus) - Zaldy Rismansyah Suparman; Pompong B. Setiadi; Nanik Kustiningsih; Putri Rahma Dayanti (Sean Institute, 2023)
Financial management and regional budget planning require carefulness and accuracy based on a priority scale to achieve short, medium and long term development goals so that they are right on target. The research aims to find implementation strategies to increase innovation, competence and performance of budget planners so that regions have the strength to realize development that is right on target. The research was carried out from July – December 2023. The research method was descriptive with a combination approach of quantitative and qualitative analysis. Data was obtained through a direct survey of respondents who had been determined deliberately. The data obtained is given a weight value based on assessment indicators obtained from the results of preliminary research. Test the validity and reliability of the data in a gradual and structured manner using a triangulation and role sharing approach. The research results are presented in the form of a spider web diagram which is equipped with illustrations of shift share gap values, root cause analysis diagrams with weighting, Pearson correlation analysis , and regression equation models obtained from the SPSS version 2.3 statistical tool.